Statistical data on the physical and mechanical properties of fibre reinforced alkali activated uncalcined earth based composite - Ojo, Emeso B.; Bello, Kabirat O.; Teixeira, Ronaldo S. [UNESP]; Onwualu, Peter A.; Savastano, Holmer [UNESP] (Elsevier, 2020)
This article presents statistical data on the reinforcing effect of three different fibres (sisal, eucalyptus pulp and polypropylene) on the physical and mechanical properties of an alkali activated natural soil produced using extrusion technique for the development of earth-based building materials. The experimental testing program involved characterisation of composite mixtures including a plain unreinforced stabilised matrix (which was plain soil mixed with alkali activator solution) as well as composite mixtures incorporating 3 volume fractions of fibres (0.5, 1.0 & 2.0 vol.%) of each fibre type. Composites were tested to evaluate physical properties (density and water absorption) and flexural response under 4-point loading in both dry and saturated conditions. The obtained values were statistically analyzed using one-way analysis of variance (ANOVA), followed by Tukey multiple comparison tests to ascertain the effect of the reinforcing fibres on the physical and mechanical properties of the composites. Results obtained show unique reinforcing effects of the different fibre types in the alkali activated matrices and the sensitivity of the earth based matrix to variations in fibre volume fraction. This data article is related to “Effects of Fibre Reinforcements on Properties of Extruded Alkali Activated Earthen Building Materials” [1].
Keywords: Alkali activation; Earth based composites; Fibre reinforced composites; Modulus of rupture; Uncalcined earth composite